2022
DOI: 10.3390/ijerph19106026
|View full text |Cite
|
Sign up to set email alerts
|

Academic Performance and the Link with Depressive Symptoms among Rural Han and Minority Chinese Adolescents

Abstract: The objectives of this paper were to examine the risk of depression and depressive symptoms among Han and minority children and adolescents in rural China, the links between academic performance and depressive symptoms, and the prevalence of these links among specific subgroups. A total of 8392 4th, 5th, and 6th grade students at 105 sample rural schools in eight low-income counties and districts in a prefectural-level city in Southwestern China were randomly selected using a three-step sampling strategy. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Accordingly, Chinese children and adolescents are expected to pursue excellent academic performance for a bright future and positive development (Wu et al, 2019;Zhou et al, 2014) owing to the Chinese traditional academy-oriented culture. Moreover, adolescents' academic performance may predict their subsequent psychosocial functioning (Adelantado-Renau et al, 2022;Sörberg Wallin et al, 2019), with similar findings reported in the Chinese context (Feng et al, 2022;Jieyi et al, 2022).…”
Section: Introductionsupporting
confidence: 70%
“…Accordingly, Chinese children and adolescents are expected to pursue excellent academic performance for a bright future and positive development (Wu et al, 2019;Zhou et al, 2014) owing to the Chinese traditional academy-oriented culture. Moreover, adolescents' academic performance may predict their subsequent psychosocial functioning (Adelantado-Renau et al, 2022;Sörberg Wallin et al, 2019), with similar findings reported in the Chinese context (Feng et al, 2022;Jieyi et al, 2022).…”
Section: Introductionsupporting
confidence: 70%
“…This cultural emphasis on academic achievement drives students to place great importance on learning knowledge at the expense of developing various competencies, resulting in poor coping skills and a tendency to develop mental health problems ( Sun et al, 2013 ; Yoon et al, 2017 ). Additional studies have shown that the depressive symptoms of college students are more likely to be affected by factors such as poverty in graduation year, family poverty, dissatisfaction with their major, poor employment prospects, single-parent families, and national minority ( Wang M. et al, 2020 ; Feng et al, 2022 ). Regarding college students’ personality traits, studies have shown that extroversion, agreeableness, conscientiousness, and openness are negatively correlated with depression, while neuroticism is positively correlated with depression ( Han, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown an increased risk of depression among Chinese college students during the COVID-19 pandemic ( Zhang et al, 2021 ). At the same time, some scholars believe that the high detection rate of depressive symptoms among Chinese college students is related to professional satisfaction, employment prospects, personality, family, ethnicity, physical, academic performance, and interpersonal relationships ( Yang and Chen, 2015 ; Wang M. et al, 2020 ; Feng et al, 2022 ). These are the important factors that affect emotions; however, why do some people become depressed while others are not affected by the same factors?…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have indicated that rural adolescents, when compared to their urban counterparts, exhibit higher rates of depressive symptomatology ( Liu et al, 2020 , Zhang et al, 2001 ). This disparity can be attributed to the relatively lower economic development in rural areas and the paucity of accessible quality healthcare and psychoeducational resources ( Yan et al, 2021 ), resulting in an augmented risk for depressive symptoms among rural youth ( Feng et al, 2022 ). Past investigations on depressive symptoms in rural adolescent populations have been region-specific (e.g., China, Australia, India) ( Black et al, 2012 , Das et al, 2021 , Li et al, 2019a ), gender-specific ( Lai et al, 2012 , Wang et al, 2011 ), and have explored the relationships between depressive symptoms and various factors such as self-harm ( Lai et al, 2021 ), internet addiction ( Shang et al, 2023 ), and academic performance ( Feng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%